2016
DOI: 10.1007/s00586-016-4405-8
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of the lower lumbar intervertebral discs and endplates: comparative analyses of new MRI data with previous findings

Abstract: This study demonstrates the potential of using MRI data to establish a standard measurement protocol for morphometric quantification of the lower lumbar intervertebral discs and vertebral endplates. These results are invaluable in characterizing comprehensive lower lumbar morphometry, which may provide crucial information for planning spinal surgeries, designing artificial intervertebral discs, and for biomechanical modeling of the low lack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 64 publications
2
30
0
Order By: Relevance
“…The finding that gait belt transfers exceed the NIOSH-recommended safe limit for compressive force is consistent with prior reports (Garg et al, 1991a, 1991b; Marras et al, 1999). In addition, some studies have reported associations between body anthropometry and the geometry of lumbar spine and paraspinal muscles (Gungor et al, 2015a, 2015b; Tang, 2013; Tang et al, 2016; Tang et al, manuscript submitted for publication); however, the relationships between anthropometric characteristics and risk of low back pain remain unclear (Frymoyer, 1992; Manchikanti, 2000; Rubin, 2007; Sesek et al, 2014), and must be addressed in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that gait belt transfers exceed the NIOSH-recommended safe limit for compressive force is consistent with prior reports (Garg et al, 1991a, 1991b; Marras et al, 1999). In addition, some studies have reported associations between body anthropometry and the geometry of lumbar spine and paraspinal muscles (Gungor et al, 2015a, 2015b; Tang, 2013; Tang et al, 2016; Tang et al, manuscript submitted for publication); however, the relationships between anthropometric characteristics and risk of low back pain remain unclear (Frymoyer, 1992; Manchikanti, 2000; Rubin, 2007; Sesek et al, 2014), and must be addressed in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…segments. Because the intervertebral space morphology dictates that artificial intervertebral space designs cannot be designed to be directly rectangular [11], this study also found that the intervertebral gap height median height in the L5/S1 and L4/5 segments compared to the right and left sides of the spine Large in the middle and small on the left and right side need to be designed to have a large middle height of the vertebral space and a small height of the vertebral space on both sides, which can improve the biomechanics of the spine.…”
Section: Discussionmentioning
confidence: 99%
“…There are examples in the scientific literature of the use of modeling to calculate the individual parameters of intervertebral discs and vertebral bodies [2,3,10,19,21,26].…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical models as relative indicators for modeling of the personal norm as a whole exist [8,22,26]. However, they ensure for the estimation of sagittal and transverse size only and don't include IVD height index, which is a key of pathological changes expression.…”
Section: Introductionmentioning
confidence: 99%